Factors Influencing Purchase Intention Towards Eco- Friendly Products - Julianti Samsudin; Lilis Seri Yana Sirun; Nor Vera Zuhairah binti Muhirdan; Yuvaneswary A/P (International ABEC, 2021)
The greatest global challenges during this modern era is to integrate environmental sustainability as healthy environments will make the people around the world healthy. It is not only for the people but also to the animals and living things. The twenty-first century threats to our environment puts wildlife populations at risk. The world is facing a lot of environmental issues today and one of the main causes is the use of non-eco-friendly packaging materials for various consumer goods is one of the problems that the world is facing today and one of the main reason is due to the widespread use of non-ecofriendly packaging of food and other goods. Since the non-ecofriendly products has been used a lot, this study aiming to identify factors that influencing purchase intention towards ecofriendly products especially in Shah Alam area. Quantitative research was adopted for this research as the research strategy. Questionnaire-survey has been used in this research with 382 sets of questionnaires distributed to the respondents to get the data required. The results show a positive influence with consumer awareness being the most influencing factors followed by environmental knowledge and product attributes. Lastly, this research will be able to help both consumers and firm to identify what’s best for the environment to create a better world with the use of more eco-friendly products.